Nano- and Macrotribological Properties of Nanoperiod Multilayer Films Deposited by Bias Sputtering - Shojiro Miyake; Mei Wang (Journal of Nanotechnology)
Carbon and boron nitride nanoperiod (C/BN)n, boron nitride and carbon (BN/C)n, carbon nitride and boron nitride nanoperiod (CN/BN)n, and boron nitride and carbon nitride (BN/CN)n ]multilayer films with a 4-nm-period multilayer structure were deposited by bias radio frequency (RF) sputtering. The substrate used for deposition was repeatedly positioned opposite graphite and boron nitride targets. Both the nanoindentation hardness and microwear resistance of the multilayer (CN/BN)n and (BN/CN)n films changed with the layer period. The multilayer films with a 4 nm period had the highest hardness and microwear resistance. The processing characteristics of the (C/BN)n and (BN/C)n films with a 4-nm-period multilayer structure were investigated using a conductive atomic force microscope (AFM) with force modulation, which permits the quantitative recording of current and frictional force as functions of applied force. The results of processing indicated that friction and surface-current measurements are effective methods of investigating multilayer nanostructural surfaces and that the method proposed in this study for micro-electro-mechanical processing systems has high precision.